The Analysis Of Elliptical Construction In The Transporter Refueled Movie: Discourse Approach - Bakti, Deddy Perdana, Dra. Malikatul Laila, M. Hum (2017)
ABSTRACT This research is about the analysis of elliptical construction found in The Transporter Refueled movie. The objectives are 1) To derive the types of elliptical construction that are found in The Transporter Refueled movie, 2) To explain the context and reason of elliptical construction that are found in The Transpoerter Refueled movie. In this research, the writer uses a descriptive qualitative research as the type of the research. The data are utterances that contain elliptical construction found in The Trasnporter Refueled movie. The writer applies observation and document analysis method in order to collect the data. Based on the result of the data analysis, the writer analyzes 41 utterances that contain elliptical construction found in The Transporter Refueled movie. From the analysis, the writer found that 1) There are three types of ellipsis found in The Transporter Refueled movie, that are nominal ellipsis, verbal ellipsis, and clausal ellipsis, 2) There are three types of context found in The Transporter Refueled movie, that are situational context, background knowledge context, and co-textual context. As the result, there will be many verbal ellipsis found in The Transporter Refueled movie. Besides, there are also identified nominal ellipsis and clausal ellipsis. Keywords:cohesion, nominal ellipsis, verbal ellipsis, clausal ellipsis